Reproduksi Living Heritage dan Regenerasi Komunitas Batik Rifa’iyah - Risqianti, Eka Dewi; Wicaksono, Harto (Umbara, 2026)
This study aims to explain the reproduction process of the living heritage of Rifa’iyah Batik in Batang Regency using Pierre Bourdieu’s theory of reproduction. The research uses qualitative methods with a descriptive design. Informants were selected through a snowball sampling technique involving senior batik artisans and younger artisans. Data were collected through participant observation, in-depth interviews, and documentation, and then analyzed using Miles and Huberman’s interactive analysis model. The findings show that the reproduction of living heritage within the Rifa’iyah Batik Community is rooted in the formation of a religious habitus instilled since childhood through spiritual habituation within the family and community environment. This habitus fosters attitudes of patience, meticulousness, and the interpretation of batik-making as an activity of spiritual value. The transmission of cultural capital becomes a key element in the sustainability of Rifa’iyah Batik. Cultural capital is manifested through the inheritance of technical skills in canting work and mastery of motif composition, which are acquired through repeated practice. Objectified cultural capital is reflected in Rifa’iyah Batik motifs such as Banji, Pelo Ati, Kawung Ndok, and Kitiran, which contain the symbolic values of KH. Ahmad Rifa’i’s teachings. Meanwhile, the field is formed within the family and within the community.